EKSISTENSI BUMN TIDAK MENGARAH PADA ETATISME - Totok Dwinur Haryanto (Universitas Slamet Riyadi, 2008)
Abstract : Engagement of the State into the economic activities comes out from the objective of the State to reach a just and prosperous society. The State is obliged not only to maintain orderly society, but is has a task well to participate in every sector of public life. The development of economic policy concerning the role and status of the State within the economic activities gave birth the idea of Etatism Economic Politics, economy politics with the Market Economy System or combination of both systems. Key words :State Owned Enterprise, Etisme.